Automatic calculation of the characteristic speeds off passenger plane - Наумов, О.В. (Proceedings of National Aviation University (archive), 2007)
Introduction of a global world communication system, navigation, surveillance / air traffic management CNS/ATM is one of directive perspective positions ICAO. In the given system elements of the flight plan are standard schemes of departure SID and arrivals STAR, approach charts “APPROACH”, go-around “GO AROUND”, flight in holding area “HOLD” and other elements. Thus control of airplane should implement both in lateral, and in the longitudinal channel, together with on thrust of engines.